1985
DOI: 10.1111/j.1445-2197.1985.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Phaeochromocytoma in Queensland—1970–83

Abstract: A statewide survey was conducted in Queensland to record all cases of phaeochromocytoma between the years of 1970 and 1983 inclusive. There were 46 cases giving an incidence of 1.55/million population per year. Twenty‐nine patients (63%) were successfully treated while 10 patients (22%) died of the tumour effects. Seven cases (15%) were found incidentally at autopsy, though at least one showed diagnostic clinical features before death. Five patients (11%) had extra adrenal phaeochromocytoma, five patients (11%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 10 publications
0
30
1
Order By: Relevance
“…Information on the epidemiology of phaeochromocytoma has been obtained from two studies carried out in defined populations with good ascertainment (Hartley & Perry-Keene 1985, Andersen et al 1988. In a statewide survey in Queensland, Australia, Hartley & Perry-Keene (1985) surveyed the characteristics of 46 cases of phaeochromocytoma presenting between 1970 and 1983.…”
Section: Phaeochromocytomamentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the epidemiology of phaeochromocytoma has been obtained from two studies carried out in defined populations with good ascertainment (Hartley & Perry-Keene 1985, Andersen et al 1988. In a statewide survey in Queensland, Australia, Hartley & Perry-Keene (1985) surveyed the characteristics of 46 cases of phaeochromocytoma presenting between 1970 and 1983.…”
Section: Phaeochromocytomamentioning
confidence: 99%
“…In a statewide survey in Queensland, Australia, Hartley & Perry-Keene (1985) surveyed the characteristics of 46 cases of phaeochromocytoma presenting between 1970 and 1983. The incidence was 1.55 per million per year.…”
Section: Phaeochromocytomamentioning
confidence: 99%
“…2 Autopsy studies show that the disease is not recognized in 20% to 75% of patients during life but represents the cause of death in half of them. 3,4 Proper diagnosis of pheochromocytoma by highly sensitive biochemical tests therefore remains of paramount importance.…”
mentioning
confidence: 99%
“…In other groups of patients, age 60 years or more was reported in 11%, 12%, 26% and 27%. 9,[25][26][27] Swedish data based on a cohort combining 439 clinical and autopsy cases have shown that 65% of the autopsy subjects were aged 60 years or more. 28 The mean age of the clinically diagnosed cases was lower than that of those diagnosed at autopsy (49 vs 66 years), and it was estimated that the incidence of pheochromocytoma per 1 million of population in Sweden was agedependent and at the age of 80 years or more it was twice as high as at the age of 50-59 years.…”
mentioning
confidence: 99%